2008
DOI: 10.1371/journal.pone.0003921
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Gene, fudoh, in the SCCmec Region Suppresses the Colony Spreading Ability and Virulence of Staphylococcus aureus

Abstract: Staphylococcus aureus colonies can spread on soft agar plates. We compared colony spreading of clinically isolated methicillin-sensitive S. aureus (MSSA) and methicillin-resistant S. aureus (MRSA). All MSSA strains showed colony spreading, but most MRSA strains (73%) carrying SCCmec type-II showed little colony spreading. Deletion of the entire SCCmec type-II region from these MRSA strains restored colony spreading. Introduction of a novel gene, fudoh, carried by SCCmec type-II into Newman strain suppressed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
61
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 28 publications
3
61
0
Order By: Relevance
“…We show that the large hospital-associated type II SCCmec element has a significant effect on the toxicity and growth rate of MRSAs. The mechanism by which the type II element reduces toxin expression is not fully understood but is possibly a consequence of the presence of the recently identified fudoh gene (Kaito et al, 2008). We believe the fitness burden associated with carrying the large type II SCCmec element is partially compensated for by the reduction in toxin expression, and that this contributes to the restriction of these MRSA strains to health-care settings where transmission is often through health-care workers and a large pool of susceptible hosts are available.…”
Section: Discussionmentioning
confidence: 99%
“…We show that the large hospital-associated type II SCCmec element has a significant effect on the toxicity and growth rate of MRSAs. The mechanism by which the type II element reduces toxin expression is not fully understood but is possibly a consequence of the presence of the recently identified fudoh gene (Kaito et al, 2008). We believe the fitness burden associated with carrying the large type II SCCmec element is partially compensated for by the reduction in toxin expression, and that this contributes to the restriction of these MRSA strains to health-care settings where transmission is often through health-care workers and a large pool of susceptible hosts are available.…”
Section: Discussionmentioning
confidence: 99%
“…Although S. aureus was originally believed to be nonmotile, recent studies have shown that this organism is capable of spreading over wet surfaces (25)(26)(27). We have previously shown that a mix of the four PSM␣ peptides can promote this so-called colony spreading phenotype (27), and we hypothesized that this relates to their strong surfactant properties (9).…”
Section: S Taphylococcus Aureus Is An Opportunistic Human Pathogen Thatmentioning
confidence: 99%
“…The PSM␤ peptides appear less important for cytolysis and inflammation but, in low concentrations, they seem to promote biofilm formation by Staphylococcus epidermidis. High amounts of the same PSM␤ peptides do, however, promote the detachment of staphylococcal cells from biofilms both in vitro and in vivo (24).Although S. aureus was originally believed to be nonmotile, recent studies have shown that this organism is capable of spreading over wet surfaces (25)(26)(27). We have previously shown that a mix of the four PSM␣ peptides can promote this so-called colony spreading phenotype (27), and we hypothesized that this relates to their strong surfactant properties (9).…”
mentioning
confidence: 99%
“…Hospital-associated methicillin-resistant S. aureus (HA-MRSA) 2 strains have lower colony-spreading ability than community-acquired MRSA (CA-MRSA) strains that cause severe diseases (10). The correlation between high colony-spreading activity and high virulence of S. aureus strains suggests that colony spreading has a role in the infectious processes of S. aureus (10).…”
mentioning
confidence: 99%
“…The correlation between high colony-spreading activity and high virulence of S. aureus strains suggests that colony spreading has a role in the infectious processes of S. aureus (10). The difference in colony-spreading activity and virulence between HA-MRSA and CA-MRSA is attributed to the virulence regulatory RNA harbored specifically in the SCCmec region of the HA-MRSA strain (11).…”
mentioning
confidence: 99%